Índice composto para avaliação da sustentabilidade de bairros - ICSB - Martins, Marcele Salles (2021)
Due to the unsustainable urban impacts, including the natural resources consumption and the peripheral population density, urban sustainability which represents the different balance of the environmental, social, and economic functions in the urban environment, it is essential and urgent for all cities. The cities need wide-ranging plans to achieve the United Nations' Sustainable Development Goals at a neighbourhood level evaluation is needed to ensure its process feasibility. An evaluation based on indicators may suggest a pathway towards sustainability and, at the same time, stimulate evaluation structure development. In order to generate a composite index of neighbourhood sustainability (CINS) to assess the existing neighbourhoods’ sustainability level, this research developed a sustainability evaluation structure. The study is an applied research with qualitative and quantitative approach and multiple case study strategy for proposition validation. Through literature review and content analysis, potential indicators were identified for the development of sustainable neighbourhoods that were submitted for expert evaluation. In the end, 12 indicators considered relevant for the intended evaluation were defined in five components. The relevant indicators build in the evaluation structure applied to five neighbourhoods as case studies, selected from a previous cluster analysis, classified by income level, and randomly picked in their respective groupings. The results generated from the assessment framework showed that they provide significant information for the sustainability level in the neighbourhood gauging, identifying the potentialities and deficiencies of the indicators that impact sustainability. The proposed structure (ICSB) allows identifying relations with specific characteristics of the neighbourhoods such as income, housing density, or others. In the case study carried out to validate the proposal, it was identified that income positively impacts the sustainability of neighbourhoods and that in neighbourhoods with higher income the indicators had a better performance. This performance was expressive related to the proximity to green areas indicator. The indicators proximity to public transportation and access to schools showed better results in neighbourhoods with lower income. In this way, the CINS helps the planning professionals and in gestion to take effective measures towards sustainable neighbourhood development.